The challenges of implementing advanced access for residents in family medicine in Quebec. Do promising strategies exist?. Issue 1 (1st January 2018) - Abou Malham, Sabina; Touati, Nassera; Maillet, Lara; Breton, Mylaine
ABSTRACT: Background : The advanced access (AA) model is a highly recommended innovation to improve timely access to primary healthcare. Despite that many studies have shown positive impacts for healthcare professionals, and for patients, implementing this model in clinics with a teaching mission for family medicine residents poses specific challenges. Objective: To identify these challenges within these clinics, as well as potential strategies to address them. Design : The authors adopted a qualitative multiple case study design, collected data in 2016 using semi-structured interviews ( N = 40) with healthcare professionals and clerical staff in four family medicine units in Quebec, and performed a thematic analysis. They validated results through a discussion workshop, involving many family physicians and residents practicing in different regions Results : Five challenges emerged from the data: 1) choosing, organizing residents' patient; 2) managing and balancing residents' appointment schedules; 3) balancing timely access with relational continuity; 4) understanding the AA model; 5) establishing collaborative practices with other health professionals. Several promising strategies were suggested to address these challenges, including clearly defining residents' patient panels; adopting a team-based care approach; incorporating the model into academic curriculum and clinical training; proactive and ongoing education of health professionals, residents, and patients; involving residents in the change process and in adjustment strategies. Conclusions : To meet the challenges of implementing AA, decision-makers should consider exposing residents to AA during academic training and clinical internships, involving them in team work on arrival, engaging them as key actors in the implementation and in intra- and inter-professional collaborative models.